Isolation and molecular identification of fungi causing stem rot disease in Bali's local legumes - Ni Made Susun Parwanayoni; Dewa Ngurah Suprapta; Nyoman Darsini; Sang Ketut Sudirga (Biogenesis: Jurnal Ilmiah Biologi, 2021)
Efforts to improve food security in Indonesia, particularly Bali, need to be supported by improvements in cultivation techniques, including the management of pests and diseases. Meanwhile, legume crops are often attacked by stem rot diseases which potentially decrease production and leads to economic losses. This disease is generally caused by the soil-borne pathogenic fungus Sclerotium rolfsii or Athelia rolfsii. The macroscopic and microscopic morphologies of these two species are the same and difficult to distinguish, hence, molecular identification is needed to differentiate between the species. Therefore, this study aims to isolate and molecularly identify the fungi causing stem rot disease in local legume plants in Bali. The methods used include isolation of pathogenic fungi from legumes showing symptoms of stem rot disease, pathogenicity test, identification of isolates with the highest virulent levels, DNA extraction, DNA amplification by PCR and electrophoresis, ITS region sequencing and computer analysis sequences. The isolation procedure identified six fungal isolates coded SKT, SKB1, SKB2 SKB3, SKL and SKN isolates. SKT isolates had the highest virulence rate as indicated by the pathogenicity test of peanut plants. Furthermore, molecular identification results show that SKT isolate is Athelia rolfsii, a similar clade with the fungi sequences in GenBank with 100% bootstrap support.